Evaluating Strategic Information Systems Planning (SISP) performance among Malaysian government agencies using organizational learning‐based model - Abu Bakar, Fazidah; Suhaimi, Mohd Adam; Hussin, Husnayati (2013)
Previous strategic information systems planning (SISP) studies have highlighted that an ideal SISP practice should emphasise on organisational learning (OL) in their SISP approach. Surprisingly, studies focusing on the extent of OL and its contextual factors are lacking. This study aims to develop and validate a model for evaluating SISP performance in the Malaysian government agencies from OL perspective. For this purpose, an SISP performance model was developed based on the absorptive capacity theory where SISP is viewed as a learning process instead of planning process. The theoretical assumption is that the quality of SISP contextual factors will influence the extent of SISP learning which eventually will influence the SISP success. The contextual factors are SISP climate, consultant expertise and CIO capability. Meanwhile, the SISP learning factors comprise of shared ICT/business knowledge and SISP process effectiveness with SISP success as the SISP performance measurement. 706 questionnaires were sent to 234 selected government agencies in Malaysia. Only 27% of the government officers responded to the questionnaire meets the criteria of this study. Measurements were initially validated using SPSS. Subsequent confirmation on the measurements and structural validity were done by adopting the Structural Equation Modeling (SEM) analyses using AMOS. The results of this study demonstrated that the hypothesised SISP performance model adequately fits the sample data which assumed the model is acceptable. Generally, the findings of this study indicated that higher level of SISP climate, consultant expertise and CIO capability positively influence the extent of SISP learning factors and later influence the SISP success. In determining the SISP success, this study revealed that it is crucial for the Malaysian government agencies to identify appropriate SISP team members based on their knowledge, skill and attitude to promote conducive SISP learning climate for effective SISP decision making.